Low serum intact parathyroid hormone level is an independent risk factor for overall mortality and major adverse cardiac and cerebrovascular events in incident dialysis patients. Issue 9 (September 2016) - Lee, Sul; Lee, Mi; Ryu, Geun; Jhee, Jong; Kim, Hyung; Park, Seohyun; Jung, Su-Young; Oh, Hyung; Park, Jung; Han, Seung; Kang, Shin-Wook; Yoo, Tae-Hyun
Abstract Summary Abnormal bone dynamics is a major risk factor for cardiovascular disease in patients with chronic kidney disease. The level of serum intact parathyroid hormone (iPTH) is widely used as a bone dynamic marker. We investigated the effect of the mean level of serum iPTH on overall mortality and cardiovascular outcomes in incident dialysis patients. Purpose Chronic kidney disease–mineral bone disorder (CKD–MBD) is a major risk factor for cardiovascular disease (CVD) in patients with end-stage renal disease (ESRD). CKD–MBD is classified as low- or high-turnover bone disease according to the bone dynamics; both are related to vascular calcification in ESRD. To evaluate the prognostic value of abnormal serum parathyroid hormone (PTH) levels on ESRD patients, we investigated the effects of time-averaged serum intact PTH (TA-iPTH) levels on overall mortality and major adverse cardiac and cerebrovascular events (MACCEs) in incident dialysis patients. Methods Four hundred thirteen patients who started dialysis between January 2009 and September 2013 at Yonsei University Health System were enrolled. The patients were divided into three groups according to TA-iPTH levels during the 12 months after the initiation of dialysis: group 1, <65 pg/ml; group 2, 65–300 pg/ml; and group 3, >300 pg/ml. Cox regression analyses were performed to determine the prognostic value of TA-iPTH for overall mortality and MACCEs. Results The mean age of the patients was 57 ± 15 years, and 222 patients (54 %) were men. During the median follow-up of 40.8 ± 29.3 months, 49 patients (12 %) died, and MACCEs occurred in 55 patients (13 %). The multivariate Cox regression analyses demonstrated that a low TA-iPTH level was an independent risk factor for both overall mortality (group 2 as reference; group 1: hazard ratio (HR) = 2.06, 95 % confidence interval (CI) = 1.11–3.83, P  = 0.023) and MACCEs (HR = 1.82, 95 % CI = 1.04–3.20, P  = 0.036) in incident dialysis patients after adjustment for confounding factors. Conclusion Low serum TA-iPTH is a useful clinical marker of both overall mortality and MACCEs in patients undergoing incident dialysis, mediated by vascular calcification.